1996
DOI: 10.1021/ic960353s
|View full text |Cite
|
Sign up to set email alerts
|

Methylation of Boron Vertices of the Cobalt Dicarbollide Anion

Abstract: The lipophilic cobalt dicarbollide anion has found uses as a weakly coordinating ion for use with Ziegler−Natta catalysts and for the extraction of dangerous radioactive isotopes from nuclear waste. A hexamethyl derivative is described which should have similar or enhanced lipophilicity, as well as methyl groups which block the B-verticies most likely to coordinate to cations or function as reaction sites during γ-ray irradiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 18 publications
0
27
0
Order By: Relevance
“…Palladium-catalyzed B ± C cross-coupling reactions on Cs[8-I-3,3'-Co(1,2-C 2 B 9 H 10 )(1',2'-C 2 B 9 H 11 )] with Grignard reagents: We were interested in checking whether the cross-coupling methodology that can be successfully used at the antipodal, B9, and/or B12 o-carborane positions [15a,b] of 9,12-I 2 -1,2-C 2 B 10 H 10 and 12-I-1,2-C 2 B 10 H 11 , at the B3 vertex of 3-I-1,2-C 2 B 10 H 11 , and at B8, B9, and B12 [27] of the [3,3'-Co(8,9,12-I 3 -…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Palladium-catalyzed B ± C cross-coupling reactions on Cs[8-I-3,3'-Co(1,2-C 2 B 9 H 10 )(1',2'-C 2 B 9 H 11 )] with Grignard reagents: We were interested in checking whether the cross-coupling methodology that can be successfully used at the antipodal, B9, and/or B12 o-carborane positions [15a,b] of 9,12-I 2 -1,2-C 2 B 10 H 10 and 12-I-1,2-C 2 B 10 H 11 , at the B3 vertex of 3-I-1,2-C 2 B 10 H 11 , and at B8, B9, and B12 [27] of the [3,3'-Co(8,9,12-I 3 -…”
Section: Resultsmentioning
confidence: 99%
“…[27] This opened up the possibility of achieving monosubstitution from [8-I-3,3'-Co(1,2-C 2 B 9 H 10 )(1',2'-C 2 B 9 H 11 )] À ( [2] À ). Figure 1 shows the numbering of the vertices for compound [2] À .…”
Section: Introductionmentioning
confidence: 99%
“…The synthesis of these compounds wasn ow possible owing to the great advances in iodine substitution on the carborane cluster. [4] Earlier we and others had demonstrated that starting from monoiodinated metallacarboranes, [4,16] alkyl derivatives can be produced by am odification of the Kumada reaction. In Scheme 1, the syntheses of [3,3'-Co(9,12-I 2 -1,2-closo-C 2 B 9 H 9 ) 2 ] À (I 4 - [1] À )a nd [3,3'-Co(9,12-(Me) 2 -1,2-closo-C 2 B 9 H 9 ) 2 ] À ((Me) 4 - [1] À ), are shown.…”
Section: Resultsmentioning
confidence: 99%
“…À , [31] [3,3'-Co-(8-Me-1,2-closo-C 2 B 9 H 9 ) 2 ] À , [31] 3,3'-Co(8,9,10-I 3 -1,2-closo-C 2 B 9 H 8 ) 2 ] À , [16] ,3'-Co(8,9,10-Me 3 -1,2-closo-C 2 B 9 H 8 ) 2 ] À , [16] were synthesized as reported in the literature. The synthesis of [3,3'-Co-(8-Me-1,2-closo-C 2 B 9 H 9 ) 2 ] À and [3,3'-Co-(9,12-I 2 -1,2-closo-C 2 B 9 H 9 ) 2 …”
Section: Methodsmentioning
confidence: 99%
“…The cobalt bis (dicarbollide) anion [3-Co-(1,2-C 2 B 9 H 11 ) 2 ] − ( Fig. 1) besides being the most investigated metallaheteroborane sandwich compound, it presents potential application in NLO [29][30][31].…”
Section: Introductionmentioning
confidence: 99%